2008
DOI: 10.1002/nau.20576
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative opening detrusor pressure is predictive of detrusor overactivity following TVT in patients with pre‐operative mixed urinary incontinence

Abstract: Higher numbers of patients are required to demonstrate the value of opening detrusor pressure in predicting post-operative overactive bladder symptoms. Opening detrusor pressure is predictive of post-operative DO after TVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 22 publications
1
27
1
Order By: Relevance
“…Recently, other investigators have also looked at predicting detrusor overactivity (DO) or voiding dysfunction after TVT. Panayi et al [28] found that the median preoperative opening detrusor pressure was higher in women with overactive bladder symptoms postoperatively. The median preoperative opening detrusor pressure also was higher in women with postoperative DO than those with a normal study.…”
Section: Can Urodynamics Assess For Risk Factors Related To Treatmentmentioning
confidence: 99%
“…Recently, other investigators have also looked at predicting detrusor overactivity (DO) or voiding dysfunction after TVT. Panayi et al [28] found that the median preoperative opening detrusor pressure was higher in women with overactive bladder symptoms postoperatively. The median preoperative opening detrusor pressure also was higher in women with postoperative DO than those with a normal study.…”
Section: Can Urodynamics Assess For Risk Factors Related To Treatmentmentioning
confidence: 99%
“…In a retrospective study of 51 patients, Panayi et al found that higher opening detrusor pressure, lower volume at DO during cystometry and higher detrusor pressure were predictive of persistent DO. (Panayi et al, 2009) Schrepferman et al evaluated 84 women undergoing a pubovaginal sling surgery for MUI. (Schrepferman et al, 2000) Of those patients, 69 had urgency symptoms.…”
Section: Preoperative Risk Factors For Mixed Urinary Incontinencementioning
confidence: 99%
“…Women reporting symptoms of OAB postoperatively had a higher preoperative opening detrusor pressure than those without OAB symptoms (33.0 cmH2O vs. 16.0 cmH2O, respectively ( P <0.05)). [22]…”
Section: Special Situationsmentioning
confidence: 99%